2014
DOI: 10.1002/2014jd021785
|View full text |Cite
|
Sign up to set email alerts
|

Using a coupled lake model with WRF for dynamical downscaling

Abstract: The Weather Research and Forecasting (WRF) model is used to downscale a coarse reanalysis (National Centers for Environmental Prediction-Department of Energy Atmospheric Model Intercomparison Project reanalysis, hereafter R2) as a proxy for a global climate model (GCM) to examine the consequences of using different methods for setting lake temperatures and ice on predicted 2 m temperature and precipitation in the Great Lakes region. A control simulation is performed where lake surface temperatures and ice cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 40 publications
(71 reference statements)
3
57
0
Order By: Relevance
“…At present, scholars pay less attention to the ice duration in TP lakes. Only a few studies analyzed the changes in the freezing date of Nam Co Lake [34], as well as lake ice structure [35], thermal conductivity [36] and ice melting date [37] in a small TP thermokarst lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, scholars pay less attention to the ice duration in TP lakes. Only a few studies analyzed the changes in the freezing date of Nam Co Lake [34], as well as lake ice structure [35], thermal conductivity [36] and ice melting date [37] in a small TP thermokarst lake.…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate estimation of ice albedo may lead to an obvious bias in the LST simulation in the coming year, subsequently affecting the regional climate modelling [24,31]. Mallard et al [34] significantly improved the simulation of Great Lakes temperatures and ice cover through progressing the ice albedo parameterizations. However, little attention has been paid to the ice albedo of TP lakes.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated approach implemented in FLake allows for the combination of high computational efficiency with a realistic representation of the major physics behind turbulent and diffusive heat exchange in the stratified water column. As a result, FLake is widely used for lake representation in the land schemes of regional climate models, being implemented, among others, into the surface schemes of the Weather Research and Forecasting Model (WRF; Mallard et al, 2014), HTESSEL (ECMWF; Dutra et al, 2010), SUR-FEX (Meteo France; Salgado and Le Moigne, 2010), and JULES (UK Met Office; Rooney and Jones, 2010). Thanks to its robustness and computational efficiency, FLake has become a standard choice in climate studies involving the feedback between inland waters and the atmosphere and is used operationally in the NWP models of the German Weather Service (DWD), the European Centre for MediumRange Weather Forecasts (ECMWF), the UK Met Office, the Swedish Meteorological and Hydrological Institute (SMHI), the Finnish Meteorological Institute (FMI), and others.…”
Section: Modelingmentioning
confidence: 99%
“…FLake has previously been coupled with many RCMs and weather prediction models (Mallard et al 2014;Martynov et al 2010;Martynov et al 2012;Mironov et al 2010). For shallow and freezing lakes, several studies showed that FLake could reproduce lake surface temperatures (LST) with and without an ice cover, as well as freeze-up and breakup dates (Kheyrollah Pour et al 2012;Martynov et al 2010;Samuelsson et al 2010).…”
Section: Lake Model: Flakementioning
confidence: 99%